HUBUNGAN GADGET TERHADAP PERKEMBANGAN SOSIAL ANAK USIA DINI - Astari, Anggun; Ismet, Syahrul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In this era of rapid and sophisticated development of technology and communication, it is undeniable that early childhood also mingles with technology, especially in the field of communication, namely gadgets. The study aims to see the relationship of gadgets to early childhood social development. The method used is quantitative with a correlational approach. The sample of this study was 53 children with total sampling. Data were collected using observation, documentation and questionnaires. Normality test, linearity, and hypothesis testing are the data analysis techniques used. The results of the study found the relationship of gadgets to early childhood social development